An introduction to orthodontics - Mitchell, Laura, 1958-; Littlewood, Simon J.; Nelson-Moon, Zararna; Dyer, Fiona (Oxford : Oxford University Press, 2013)
Providing an introduction to current thinking and practice in orthodontics, this text covers all aspects of the field, including clinical practice and treatment planning.
Includes bibliographical references and index.
Keywords: Orthodontics